Amidoxime functionalized MXene / CoZn-MOF heterostructure flowing electrode, preparation method thereof and application of amidoxime functionalized MXene / CoZn-MOF heterostructure flowing electrode in efficient adsorption of uranium in wastewater
By growing CoZn-MOF on MXene nanosheets and grafting amine oxygen functional groups, a flow electrode of amidoxime-functionalized MXene/CoZn-MOF heterostructure is formed, which solves the problem of limited uranium removal capability in traditional capacitive deionization technology. Efficient, continuous uranium ion removal and low-energy water recovery are achieved.
Patent Information
- Application Number
- CN202411618286.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Due to the static characteristics of the electrode, traditional capacitive deionization technology has problems such as limited ion removal capability, complex preparation processes and discontinuity of adsorption-desorption processes, making it difficult to efficiently remove uranium in seawater.
A flow electrode using an amidoxime-functionalized MXene/CoZn-MOF heterostructure is used to grow CoZn-MOF on MXene nanosheets and graft amine oxygen functional groups on the MOF/MXene composite to form a stable complex. Improve uranium capture efficiency.
It achieves efficient and continuous uranium ion removal, improves uranium removal rate and electrochemical adsorption performance, while reducing energy consumption and operating costs.
Smart Images

Figure CN119349720A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sewage treatment, and in particular relates to an amidoxime-functionalized MXene / CoZn-MOF heterostructured flow electrode, a preparation method thereof, and application thereof in efficiently adsorbing uranium in wastewater. Background Art
[0002] The increasing demand for nuclear energy and the limited terrestrial uranium resources have prompted the scientific community to explore other sources. Seawater contains about 3.3 μg / L of uranium, which is a huge and untapped resource. However, due to the extremely low uranium concentration and the presence of high concentrations of competing ions such as sodium, magnesium and calcium, the extraction of uranium from seawater faces major challenges. To address these issues, various water treatment technologies such as reverse osmosis, thermal distillation and electrodialysis have been developed. However, these methods are energy-intensive and have significant processing costs, and efficient and cost-effective water recovery technologies are urgently needed.
[0003] In recent years, capacitive deionization (CDI, also known as electrosorption) has shown great promise as a technology for effectively removing charged ions from aqueous solutions. CDI has the advantages of being cost-effective, environmentally friendly, energy-saving, easy to operate, and reusable. However, conventional CDI has limitations in ion removal capacity due to the static nature of the electrodes. On the one hand, the complex preparation process of the fixed electrodes contains about 20% of the components of carbon black and binders, which reduces the ion adsorption capacity. On the other hand, after ion electrosorption, the electrodes need to be regenerated by short circuiting or polarity reversal, making the adsorption-desorption process discontinuous. Compared with conventional methods, the flowing electrode capacitive deionization (FCDI) technology has many advantages, including simplified electrode preparation, higher adsorption capacity, continuous ion removal, and higher water recovery. The evolution of electrode materials has significantly affected the development of efficient FCDI technology. Common carbon-based FCDI electrode materials, such as activated carbon, graphene, carbon nanotubes, and biomass-derived carbon, have inherent limitations, including low selectivity, unsatisfactory desalination efficiency, common ion rejection, and incompatibility with actual seawater environments, which significantly hinder their widespread application.
[0004] Faradaic nanomaterials, including metal-organic frameworks (MOFs), Prussian blue analogs, conducting polymers and their heterostructures, have been widely explored as high-performance pseudocapacitive CDI electrodes. In particular, bimetallic MOFs, with high theoretical capacitance, better stability and unique heterostructures, have demonstrated excellent CDI performance. Nevertheless, MOF-based CDI water treatment technology is still limited by insufficient capture capacity, poor selectivity and low intrinsic electrochemical conductivity in practical applications. Summary of the invention
[0005] In order to solve the above technical problems, the present invention proposes an amidoxime-functionalized MXene / CoZn-MOF heterostructured flow electrode and its preparation method and application in the efficient adsorption of uranium in wastewater. The technical solution of the present invention has the advantages of many micropores, high specific capacitance, high conductivity, strong fluidity, high uranium removal rate and low energy consumption.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention:
[0008] A method for preparing a mobile electrode of amidoxime functionalized MXene / CoZn-MOF heterostructure comprises the following steps:
[0009] (1) MXene nanosheets (Ti3C2T x powder) was dispersed in methanol, and after ultrasonic treatment, polyvinyl pyrrolidone (PVP) was added and stirred to obtain a mixture, and then zinc nitrate (Zn(NO3)2·6H2O) and cobalt nitrate (Co(NO3)2·6H2O) were added and ultrasonic treatment was performed to obtain a mixed solution a;
[0010] (2) adding a methanol solution of imidazole-2-carboxaldehyde to the mixed solution a, and stirring and mixing at room temperature to obtain a mixed solution b;
[0011] (3) Adding amidoxime-functionalized diaminomaleonitrile to the mixed solution b, stirring for reaction, aging, centrifuging, washing, and freeze-drying to obtain the amidoxime-functionalized MXene / CoZn-MOF heterostructure flow electrode.
[0012] MXene nanosheets are two-dimensional metal carbides and nitrides with excellent electrical conductivity, rich polar functional groups and excellent mechanical flexibility, and are ideal support and electrode materials. Bimetallic MOFs grown in situ on MXene nanosheets have shown great potential in capacitive deionization. The present invention combines the high surface area and selective adsorption characteristics of MOF with the electrical conductivity and flexibility of MXene by integrating CoZn-MOF and MXene, preventing restacking and ensuring efficient charge transfer, thereby improving the performance of CDI electrodes. In order to further improve the selectivity of uranium adsorption, aminooxy functional groups are further grafted on the MOF / MXene composite material, and the amidoxime group improves the uranium capture efficiency by forming a stable complex with the hexavalent uranium ion U(VI). The high electrical conductivity and mechanical strength of MXene nanosheets ensure the stability and durability of the material in the marine environment and prevent structural damage. Therefore, the rational assembly of bimetallic MOF materials and MXene nanosheets with amidoxime groups has broad application prospects in seawater uranium extraction.
[0013] Furthermore, the preparation method of the amidoxime functionalized diaminomaleonitrile comprises the following steps:
[0014] NH2OH·HCl and K2CO3 are dissolved in an ethanol aqueous solution to obtain a mixed solution, diaminomaleonitrile is added to the mixed solution, and the mixture is heated under nitrogen protection for reaction. After the reaction is completed, a sample is collected by centrifugation, washed, and freeze-dried to obtain the amidoximated diaminomaleonitrile.
[0015] Furthermore, in the preparation process of the amidoxime functionalized diaminomaleonitrile, the mass ratio of NH2OH·HCl to K2CO3 is 1:1; and / or
[0016] The mass volume ratio of the NH2OH·HCl to the ethanol aqueous solution is 1 g: (100-120) mL; and / or
[0017] The mass volume ratio of the diaminomaleonitrile to the ethanol aqueous solution is (1-4) mg:1 mL; and / or
[0018] The temperature-raising reaction is carried out by heating the temperature to 90° C. for 8 hours.
[0019] Furthermore, during the preparation of the amidoxime functionalized diaminomaleonitrile, the volume ratio of ethanol to water in the ethanol aqueous solution is 9:1.
[0020] Furthermore, during the preparation of the amidoxime functionalized diaminomaleonitrile, washing is performed with an ethanol aqueous solution, wherein the volume ratio of ethanol to water in the ethanol aqueous solution is (1-5):1.
[0021] Further, in the preparation process of the amidoxime functionalized MXene / CoZn-MOF heterostructure flow electrode, the mass ratio of the MXene nanosheets to polyvinyl pyrrolidone is (0.8-6):2; and / or
[0022] The mass ratio of the MXene nanosheets to zinc nitrate and cobalt nitrate is (80-600):307:150.
[0023] Further, in the preparation process of the amidoxime functionalized MXene / CoZn-MOF heterostructure flow electrode, the mass ratio of the amidoxime functionalized diaminomaleonitrile to imidazole-2-carboxaldehyde is (100-800):493; and / or
[0024] The mass ratio of imidazole-2-carboxaldehyde to MXene nanosheets is 493:(80-600).
[0025] Further, during the preparation of the amidoxime functionalized MXene / CoZn-MOF heterostructure flow electrode, 0.08 g to 0.6 g of MXene nanosheets were dispersed in 40 mL of methanol; and / or
[0026] The formaldehyde solution of imidazole-2-carboxaldehyde is prepared by dissolving 493 mg of imidazole-2-carboxaldehyde in 20 mL of methanol solution.
[0027] Furthermore, during the preparation of the amidoxime-functionalized MXene / CoZn-MOF heterostructure flow electrode, the stirring reaction in step (3) was carried out at a temperature of 60° C. and for a time of 2 h.
[0028] Further, in the preparation process of the amidoxime functionalized MXene / CoZn-MOF heterostructure flow electrode, the centrifugation in step (3) is centrifugation at a speed of 8000-12000 rpm for 5-10 min; and / or
[0029] The washing is performed by washing 3-6 times with a mixed solution of N,N-dimethylformamide and methanol in a volume ratio of 1:1.
[0030] The second technical solution of the present invention:
[0031] A flow electrode of amidoxime-functionalized MXene / CoZn-MOF heterostructure is prepared according to the above preparation method.
[0032] The third technical solution of the present invention:
[0033] A flowing electrode capacitive deionization (FCDI) system, wherein the flowing electrode of the flowing electrode capacitive deionization system is the flowing electrode of the amidoxime functionalized MXene / CoZn-MOF heterostructure.
[0034] Furthermore, the FCDI system includes the amidoxime functionalized MXene / CoZn-MOF heterostructure flow electrode, a first current collector, an anion exchange membrane, a gasket, a cation exchange membrane and a second current collector.
[0035] The fourth technical solution of the present invention:
[0036] A method for efficiently adsorbing uranium in wastewater adopts the mobile electrode capacitive deionization system.
[0037] Furthermore, the operation mode of the FCDI system is a short-circuit closed cycle mode, and the effective contact area between the flow electrode and the anion exchange membrane / cation exchange membrane in the FCDI system is 22.8 cm 2 ; and / or
[0038] The flow rate of the flowing electrode and the inlet water in the flowing electrode capacitive deionization system is 10 mL / min; and / or
[0039] The constant operating voltage of the mobile electrode capacitive deionization system is 1.2V; and / or
[0040] The uranyl ion content in the wastewater body is ≥200 mg U / L.
[0041] Compared with the prior art, the present invention has the following advantages and technical effects:
[0042] 1. The amidoxime-functionalized MXene / CoZn-MOF heterostructured flow electrode prepared by the present invention exhibits extremely high uranium removal efficiency and can effectively capture uranium ions in seawater in a short time. This rapid uranium capture capability gives it a significant advantage in uranium resource extraction, especially in application scenarios where large amounts of seawater need to be processed quickly.
[0043] 2. The amidoxime-functionalized MXene / CoZn-MOF heterostructured flow electrode prepared by the present invention exhibits excellent durability and maintains good performance after multiple cycles. This reusable property means that the material can continue to work in practical applications without frequent replacement, thereby reducing operating costs and improving economic benefits. This makes the electrode an ideal choice for long-term use, especially in resource-limited environments.
[0044] 3. The amidoxime-functionalized MXene / CoZn-MOF heterostructured flow electrode prepared by the present invention has a hierarchical porous structure, which provides good conditions for the selective adsorption of uranium ions, promotes the rapid migration of ions, improves the selectivity of uranium ions, and helps to improve the overall electrochemical adsorption performance. In addition, amidoxime functionalization further enhances the affinity of the material for uranium, so that during the dynamic adsorption process, the electrode can more effectively capture uranium ions, thereby improving the extraction efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0046] Figure 1 The SEM images of the amidoxime-functionalized MXene / CoZn-MOF heterostructure flow electrode prepared in Example 1 and the MXene nanosheet used in Example 1, wherein (a) is a MXene nanosheet, and (b) is an amidoxime-functionalized MXene / CoZn-MOF heterostructure flow electrode;
[0047] Figure 2 The flow electrode (Ti3C2T x / CoZn-MOF-AO) FTIR characterization diagram;
[0048] Figure 3 The flow electrode (Ti3C2T x / CoZn-MOF-AO) XRD characterization diagram;
[0049] Figure 4 The flow electrode (Ti3C2T x / CoZn-MOF-AO) XPS characterization diagram;
[0050] Figure 5 The amidoxime-functionalized MXene / CoZn-MOF heterostructure flow electrode (Ti3C2T x / CoZn-MOF-AO) cycle regeneration performance diagram;
[0051] Figure 6 It is a structural diagram of the FCDI system;
[0052] Figure 7 The flow electrode (Ti3C2T x / CoZn-MOF-AO) removal efficiency and energy consumption during the electrosorption process as a function of applied voltage;
[0053] Figure 8 The flow electrode (Ti3C2T x / CoZn-MOF-AO) removal efficiency as a function of pH value;
[0054] Fig. 9 A real seawater adsorption experiment was conducted on the mobile electrode prepared in Example 1 / Comparative Example 1, and a comparison chart of the adsorption effects of the adsorption materials prepared in Example 1 and Comparative Example 1 on real seawater spiked with uranium is shown;
[0055] Fig.10 This is a comparison chart of the selective adsorption of different metal elements in simulated water samples by the mobile electrode prepared in Example 1;
[0056] Fig.11This is a diagram showing the adsorption effect of hexavalent uranium on the mobile electrode prepared in Example 1 after 20 cycles of regeneration;
[0057] Fig.12 This is a comparison chart of the adsorption effects of the mobile electrodes prepared in Examples 1-8 and Comparative Examples 1-3 in the real seawater spiked uranium adsorption experiment. DETAILED DESCRIPTION
[0058] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0059] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0060] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0061] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0062] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0063] The room temperature in the embodiments of the present invention refers to "25±3° C.", and all raw materials used are commercially available.
[0064] The technical solution of the present invention is further illustrated by the following embodiments.
[0065] Example 1
[0066] (1) NH2OH·HCl and K2CO3 are dissolved in an ethanol aqueous solution (the volume ratio of ethanol to water is 9:1) to obtain a mixed solution, diaminomaleonitrile is added to the mixed solution, and the mixture is heated to 90°C under nitrogen protection for reaction for 8 hours. After the reaction is completed, the sample is collected by centrifugation, washed with an ethanol aqueous solution (the volume ratio of ethanol to water is 5:1), and freeze-dried to obtain amidoximated diaminomaleonitrile; wherein the mass ratio of NH2OH·HCl to K2CO3 is 1:1, the mass volume ratio of NH2OH·HCl to the ethanol aqueous solution is 1 g:100 mL, and the mass volume ratio of diaminomaleonitrile to the ethanol aqueous solution is (4 mg:1 mL;
[0067] (2) 80 mg of MXene nanosheets (Ti3C2T x powder) was dispersed in 40 mL of methanol, and after ultrasonic treatment for 20 min, 200 mg of PVP was added and stirred for 30 min to obtain a mixture, and then 307 mg of Zn(NO3)2·6H2 and 150 mg of Co(NO3)2·6H2O were added and ultrasonic treatment was performed for 20 min to obtain a mixed solution a;
[0068] (3) adding 20 mL of methanol solution containing 493 mg of imidazole-2-carboxaldehyde to the mixed solution a prepared above, and stirring the mixture at room temperature for 1 h to obtain a mixed solution b;
[0069] (4) Add 0.5 g of amidoxime-functionalized diaminomaleonitrile prepared in step (1) to the prepared mixed solution b, stir at 60° C. for 2 h, age for 4 h, centrifuge at 10,000 rpm for 10 min, wash, and freeze-dry for 48 h to obtain Ti3C2T x / CoZn-MOF-AO (MMA) complex, which is a flow electrode of amidoxime-functionalized MXene / CoZn-MOF heterostructure.
[0070] Example 2
[0071] The amount of MXene nanosheets used in step (2) is 0.20 g, and the remaining steps remain the same as in Example 1.
[0072] Example 3
[0073] The amount of MXene nanosheets used in step (2) is 0.40 g, and the remaining steps remain the same as in Example 1.
[0074] Example 4
[0075] The amount of MXene nanosheets used in step (2) is 0.60 g, and the remaining steps remain the same as in Example 1.
[0076] Example 5
[0077] The amount of MXene nanosheets used in step (2) is 0.10 g, and the remaining steps remain the same as in Example 1.
[0078] Example 6
[0079] In step (4), the amount of amidoxime-functionalized diaminomaleonitrile used is 0.1 g, and the remaining steps remain the same as in Example 2.
[0080] Example 7
[0081] In step (4), the amount of amidoxime-functionalized diaminomaleonitrile used is 0.3 g, and the remaining steps are the same as those in Example 2.
[0082] Example 8
[0083] In step (4), the amount of amidoxime-functionalized diaminomaleonitrile used is 0.6 g, and the remaining steps are the same as those in Example 2.
[0084] Example 9
[0085] In step (4), the amount of amidoxime-functionalized diaminomaleonitrile used is 0.8 g, and the remaining steps are the same as those in Example 2.
[0086] Comparative Example 1
[0087] The same as Example 1, except that MXene nanosheets and amidoxime-functionalized diaminomaleonitrile are not added, and the method specifically comprises the following steps:
[0088] (1) Add 200 mg of PVP to 40 mL of methanol and stir for 30 min to obtain a mixture, then add 307 mg of Zn(NO3)2·6H2) and 150 mg of Co(NO3)2·6H2O, and treat with ultrasound for 20 min to obtain a mixed solution a;
[0089] (2) adding 20 mL of methanol solution containing 493 mg of imidazole-2-carboxaldehyde to the mixed solution a prepared above, and stirring the mixture at room temperature for 1 h to obtain a mixed solution b;
[0090] (3) The prepared mixed solution b was stirred at 60° C. for 2 h, aged for 4 h, centrifuged at 10,000 rpm for 10 min, and then washed and freeze-dried for 48 h to obtain a product, namely a mobile electrode.
[0091] Comparative Example 2
[0092] The same as Example 1, except that amidoxime-functionalized diaminomaleonitrile is not added, and the method specifically comprises the following steps:
[0093] (1) 80 g of MXene nanosheets (Ti3C2T xpowder) was dispersed in 40 mL of methanol, and after ultrasonic treatment for 20 min, 200 mg of PVP was added and stirred for 30 min to obtain a mixture, and then 307 mg of Zn(NO3)2·6H2) and 150 mg of Co(NO3)2·6H2O were added and ultrasonic treatment was performed for 20 min to obtain a mixed solution a;
[0094] (2) adding 20 mL of methanol solution containing 493 mg of imidazole-2-carboxaldehyde to the mixed solution a prepared above, and stirring the mixture at room temperature for 1 h to obtain a mixed solution b;
[0095] (3) The prepared mixed solution b was stirred at 60° C. for 2 h, aged for 4 h, centrifuged at 10,000 rpm for 10 min, and then washed and freeze-dried for 48 h. The obtained product was the mobile electrode.
[0096] Comparative Example 3
[0097] Same as Example 1, except that the isomeric mass of amidoxime functionalized diaminomaleonitrile is replaced by diaminomaleonitrile.
[0098] Performance Testing
[0099] The amidoxime-functionalized MXene / CoZn-MOF heterostructured flow electrode prepared in Example 1 and the MXene nanosheets used in Example 1 were subjected to scanning electron microscopy (SEM) testing experiments. The results are shown in Figure 1 , wherein (a) is a MXene nanosheet, and (b) is a flow electrode of an amidoxime-functionalized MXene / CoZn-MOF heterostructure. It can be seen that the flow electrode of the amidoxime-functionalized MXene / CoZn-MOF heterostructure prepared in Example 1 of the present invention has a rougher surface and unique nanostructured particles.
[0100] Example 1 The amidoxime-functionalized MXene / CoZn-MOF heterostructured flow electrode (Ti3C2T x / CoZn-MOF-AO) is shown in the FTIR characterization diagram Figure 2 , it can be seen that the Fourier transform infrared spectroscopy (FT-IR) of the mobile electrode of the amidoxime-functionalized MXene / CoZn-MOF heterostructure reveals the -OH, C=N and NH vibration peaks.
[0101] Example 1 The amidoxime-functionalized MXene / CoZn-MOF heterostructured flow electrode (Ti3C2T x / CoZn-MOF-AO) is shown in the XRD characterization diagram Figure 3 It can be seen that Ti3C2T xThe diffraction peak of / CoZn-MOF-AO is Ti3C2T x The main peak of MXene (002) and the main peak of CoZn-MOF indicate the coexistence of two phases.
[0102] Example 1 The amidoxime-functionalized MXene / CoZn-MOF heterostructured flow electrode (Ti3C2T x / CoZn-MOF-AO,MMA) XPS characterization diagram is shown in Figure 4 It can be seen that Ti3C2T x The surface of / CoZn-MOF-AO is mainly composed of C, N, Co, Zn, Ti and O.
[0103] The amidoxime-functionalized MXene / CoZn-MOF heterostructure flow electrode (Ti3C2T x / CoZn-MOF-AO) was used for electrochemical cyclic voltammetry performance test, and the cycle regeneration performance diagram is shown in Figure 5 It can be seen that Ti3C2T x / CoZn-MOF-AO has a specific capacitance of up to 106.04F / g, showing good electrochemical performance.
[0104] Application Example 1
[0105] Construct the FCDI system. The structural diagram of the FCDI system is as follows: Figure 6 As shown, the mobile electrode prepared in Example 1 was pumped into the cathode electrode chamber and the anode electrode chamber of the FCDI system at a flow rate of 10 mL / min, a constant voltage of 0.2-1.6 V was supplied, and then a U(VI) solution with an initial concentration of 200 mg U / L and a pH of 5 was pumped in at a flow rate of 20 mL / min. A water sample was taken every half an hour for uranium concentration detection, and the detection method was inductively coupled plasma optical emission spectrometer (ICP-OES), and then the uranyl ion removal performance and system energy consumption of the mobile electrode prepared in Example 1 were measured.
[0106] Example 1 The amidoxime-functionalized MXene / CoZn-MOF heterostructured flow electrode (Ti3C2T x The variation of adsorption amount of / CoZn-MOF-AO) with applied voltage during the electrosorption process is shown in Figure 7 It can be seen that as the applied voltage increases, the adsorption of uranyl ions by the material also increases. However, considering that the electrolysis voltage of water is 1.23 V and the energy consumption problem, the constant voltage power supply of the FCDI system is set to 1.2 V.
[0107] Application Example 2
[0108] An FCDI system was constructed, and the mobile electrode prepared in Example 1 was pumped into the cathode electrode chamber and the anode electrode chamber of the FCDI system at a flow rate of 10 mL / min, respectively. A constant voltage of 1.2 V was supplied, and then a U(VI) solution with an initial concentration of 200 mg U / L was pumped in at a flow rate of 20 mL / min. A water sample was taken every half an hour for uranium concentration detection using an inductively coupled plasma optical emission spectrometer (ICP-OES). The uranyl ion removal performance and system energy consumption of the mobile electrode prepared in Example 1 were investigated.
[0109] Example 1 The amidoxime-functionalized MXene / CoZn-MOF heterostructured flow electrode (Ti3C2T x The variation of adsorption amount of / CoZn-MOF-AO with pH value is shown in Figure 8 It can be seen that in the pH range of 3-6, Ti3C2T x The complex of CoZn-MOF-AO and U(VI) has high stability under acidic conditions, and the adsorption efficiency of uranium is maintained above 95%. When the pH is 7-10, the main form of uranium in the air is (UO2)2CO3(OH)3 - Due to the Coulomb repulsion between the uranium with the same charge and the adsorbent surface, Ti3C2T x The adsorption efficiency of / CoZn-MOF-AO decreased.
[0110] Application Example 3
[0111] The flow electrode prepared in Example 1 / Comparative Example 1 was subjected to a real seawater spiked uranium adsorption experiment. The adsorption effect comparison of the adsorption materials prepared in Example 1 and Comparative Example 1 on real seawater spiked uranium is shown in FIG. Fig. 9 It can be seen that the adsorption material of Example 1 has unique and excellent adsorption performance for hexavalent uranium, while the adsorption performance of Comparative Example 1 is very poor.
[0112] Application Example 4
[0113] An FCDI system was constructed, and the mobile electrode prepared in Example 1 was pumped into the cathode electrode chamber and the anode electrode chamber of the FCDI system at a flow rate of 10 mL / min, respectively. A constant voltage of 1.2 V was supplied, and then a mixed solution of U(VI), Ca, Cu, Na, Mg, V, K and Fe with an initial concentration of 200 mg U / L was pumped in at a flow rate of 20 mL / min. The pH was 5, and a water sample was taken every half an hour for uranium concentration detection. The detection method was inductively coupled plasma optical emission spectrometer (ICP-OES), and then the uranyl ion removal performance and system energy consumption of the mobile electrode prepared in Example 1 were measured.
[0114] The comparison of the selective adsorption of different metal elements in the simulated water sample by the mobile electrode prepared in Example 1 is shown in Fig.10 It can be seen that the FCDI system based on the flow electrode of Example 1 has excellent selectivity in wastewater solutions containing various ions.
[0115] Application Example 5
[0116] Regeneration experiment: A FCDI system was constructed, and the mobile electrode prepared in Example 1 was pumped into the cathode electrode chamber and the anode electrode chamber of the FCDI system at a flow rate of 10 mL / min, respectively. A constant voltage of 1.2 V was supplied, and then a U(VI) solution with an initial concentration of 200 mg U / L and a pH of 5 was pumped in at a flow rate of 20 mL / min. A water sample was taken every 125 min for uranium concentration detection using an inductively coupled plasma optical emission spectrometer (ICP-OES). The uranyl ion removal performance and system energy consumption of the mobile electrode prepared in Example 1 were investigated.
[0117] The adsorption effect of the mobile electrode prepared in Example 1 on hexavalent uranium after 20 cycles of regeneration was measured. The results are shown in Fig.11 It can be seen that the cycling performance of the flow electrode is crucial. After 20 adsorption-desorption cycles, the flow electrode prepared in Example 1 still retains 90.12% of the initial adsorption performance. This high retention of adsorption performance illustrates the uniform distribution of electrons on the flow electrode and the regeneration of adsorption sites under long-term cycling.
[0118] Application Example 6
[0119] The flow electrodes prepared in Examples 1-8 and Comparative Examples 1-3 were subjected to a real seawater spiked uranium adsorption experiment. The adsorption effect comparison diagram is shown in FIG. Fig.12 It can be seen that the adsorption materials of Examples 1-8 have unique and excellent adsorption properties for hexavalent uranium, and Example 1 has the best adsorption performance, but all of them are higher than the comparative example, indicating that the present invention has universal applicability. The prepared amidoxime-functionalized MXene / CoZn-MOF heterostructured flow electrode exhibits extremely high uranium removal efficiency and can effectively capture uranium ions in seawater in a short time. This rapid uranium capture ability gives it a significant advantage in uranium resource extraction, especially in application scenarios that require rapid processing of large amounts of seawater.
[0120] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a mobile electrode of amidoxime-functionalized MXene / CoZn-MOF heterostructure, characterized in that: The following steps are involved: (1) dispersing MXene nanosheets in methanol, adding polyvinyl pyrrolidone and stirring to obtain a mixture after ultrasonic treatment, then adding zinc nitrate and cobalt nitrate, and ultrasonic treatment to obtain a mixed solution a; (2) adding a methanol solution of imidazole-2-carboxaldehyde to the mixed solution a, and stirring and mixing at room temperature to obtain a mixed solution b; (3) Adding amidoxime-functionalized diaminomaleonitrile to the mixed solution b, stirring for reaction, aging, centrifuging, washing, and freeze-drying to obtain the amidoxime-functionalized MXene / CoZn-MOF heterostructure flow electrode.
2. The method for preparing the amidoxime functionalized MXene / CoZn-MOF heterostructure flow electrode according to claim 1, characterized in that: The preparation method of the amidoxime functionalized diaminomaleonitrile comprises the following steps: NH2OH·HCl and K2CO3 are dissolved in an ethanol aqueous solution to obtain a mixed solution, diaminomaleonitrile is added to the mixed solution, and the mixture is heated under nitrogen protection for reaction. After the reaction is completed, a sample is collected by centrifugation, washed, and freeze-dried to obtain the amidoximated diaminomaleonitrile.
3. The method for preparing the amidoxime functionalized MXene / CoZn-MOF heterostructure flow electrode according to claim 2, characterized in that: The mass ratio of NH2OH·HCl to K2CO3 is 1:1; and / or The mass volume ratio of the NH2OH·HCl to the ethanol aqueous solution is 1 g: (100-120) mL; and / or The mass volume ratio of the diaminomaleonitrile to the ethanol aqueous solution is (1-4) mg:1 mL; and / or The temperature-raising reaction is carried out by heating the temperature to 90° C. for 8 hours.
4. The method for preparing the amidoxime functionalized MXene / CoZn-MOF heterostructure flow electrode according to claim 1, characterized in that: The mass ratio of the MXene nanosheets to polyvinyl pyrrolidone is (0.8-6):2; and / or The mass ratio of the MXene nanosheets to zinc nitrate and cobalt nitrate is (80-600):307:
150.
5. The method for preparing the amidoxime functionalized MXene / CoZn-MOF heterostructure flow electrode according to claim 1, characterized in that: The mass ratio of the amidoxime functionalized diaminomaleonitrile to imidazole-2-carboxaldehyde is (100-800):493; and / or The mass ratio of imidazole-2-carboxaldehyde to MXene nanosheets is 493:(80-600).
6. The method for preparing the amidoxime functionalized MXene / CoZn-MOF heterostructure flow electrode according to claim 1, characterized in that: The stirring reaction temperature in step (3) is 60° C. and the time is 2 h.
7. A flow electrode of amidoxime-functionalized MXene / CoZn-MOF heterostructure, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 6.
8. A mobile electrode capacitive deionization system, characterized in that: The mobile electrode of the mobile electrode capacitive deionization system is the mobile electrode of the amidoxime functionalized MXene / CoZn-MOF heterostructure as described in claim 7.
9. A method for efficiently adsorbing uranium in wastewater, characterized in that: The mobile electrode capacitive deionization system of claim 8 is used.
10. The method for efficiently adsorbing uranium in wastewater according to claim 9, characterized in that: The effective contact area between the mobile electrode and the anion exchange membrane and the cation exchange membrane in the mobile electrode capacitive deionization system is 22.8 cm 2 ; and / or The flow rate of the flowing electrode and the inlet water in the flowing electrode capacitive deionization system is 10 mL / min; and / or The constant operating voltage of the mobile electrode capacitive deionization system is 1.2V; and / or The uranyl ion content in the wastewater body is ≥200 mg U / L.
Citation Information
Patent Citations
Amidoxime group modified MOF material and preparation method thereof
CN110479213A
Amidoxime-group-modified cyclodextrin / sodium alginate gel ball composite adsorption material as well as preparation method and application thereof
CN112044404A
Carbon-assembled zinc sulfide and cobalt sulfide hollow nano polyhedral framework material as well as preparation and application thereof
CN112366298A
MOF-coated PVP-derived Co and N co-doped porous carbon and battery
CN115763848A
Flowing electrode liquid, preparation method thereof and application of flowing electrode liquid in acid mine wastewater treatment
CN118324265A
Cited By
Efficient selective continuous flow removal system and method for uranium through cooperation of electro-adsorption and alternating current
CN120117711A
Hollow-cage CoZn / C-coated Ti3C2Tx / TiO2 composite material, preparation method and application
CN121780128A
Cobalt single atom loaded polyphosphazene / MXene self-supporting electrode and preparation method and application thereof
CN122079313A